Thyroid Hormone Changes in Early Kidney Transplantation and Its Correlation with Delayed Graft Function - Hekmat, Reza; Javadi, Zahra; Layghian Javan, Malihe; Sanadgol, Hooshang; Gholami, Farhad; Mohebbi, Mahmoud; Zeraati, Abbas Ali; Ahmadnia, Hassan; Tabarraiei, Hamid; Baradaran, Mahsa; Mojahedi, Mohammad Javad (Urology Journal, 2010)
Introduction: Thyroid hormones affect kidney function and may alter with changes in kidney function, as well. We evaluated changes in serum levels of triiodothyronine (T3), thyroxin (T4), and thyroid-stimulating hormone (TSH) early after kidney transplantation and their relationship with delayed graft function (DGF).Materials and Methods: Fifty-five consecutive kidney allograft recipients were enrolled in the study. Serum levels of T3, T4, and TSH were measured on the day before transplantation, and also on posttransplant days 1, 3, 7, 14, and 21. Results were compared between patients with a normal allograft function and those with DGF. Results: The mean T3 level decreased from 110.41 ± 49.79 ng/dL before transplantation to 80.78 ± 51.42 ng/dL on the 1st day after transplantation (P = .04), while T4 reduction reached a significant level on the 3rd day after transplantation (8.27 ± 3.27µg/dL to 5.50 ± 2.57 µg/dL, P = .004). Patients with DGF experienced a significantly greater decrease in the serum level of T3 at the end of the 1st week after transplantation compared with patients with normal kidney function (P = .02). This significant decrease in T3 continued until the end of the 2nd week. Serum levels of T4 reduced comparably in the two groups, until the end of the 1st week, when it showed a significantly more reduction in the patients with DGF (P = .04).Conclusion: Both T3 and T4 reduced early after kidney transplantation, and this reduction was significantly more prominent in those with DGF. This is compatible with a consequence rather than a cause of DGF, explained in the setting of sick euthyroid syndrome.